2006
DOI: 10.1128/mcb.00729-06
|View full text |Cite
|
Sign up to set email alerts
|

Putative “Stemness” Gene Jam-B Is Not Required for Maintenance of Stem Cell State in Embryonic, Neural, or Hematopoietic Stem Cells

Abstract: Many genes have been identified that are specifically expressed in multiple types of stem cells in their undifferentiated state. It is generally assumed that at least some of these putative "stemness" genes are involved in maintaining properties that are common to all stem cells. We compared gene expression profiles between undifferentiated and differentiated embryonic stem cells (ESCs) using DNA microarrays. We identified several genes with much greater signal in undifferentiated ESCs than in their differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 44 publications
(56 reference statements)
3
50
0
Order By: Relevance
“…Southern blot analysis was done as described previously [10] using 5 0 and 3 0 flanking regions of nucleostemin gene. For genotyping by PCR, three different primers were used to amplify a portion of wild-type nucleostemin gene and a boundary region of the b-geo reporter gene.…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Southern blot analysis was done as described previously [10] using 5 0 and 3 0 flanking regions of nucleostemin gene. For genotyping by PCR, three different primers were used to amplify a portion of wild-type nucleostemin gene and a boundary region of the b-geo reporter gene.…”
Section: Genotypingmentioning
confidence: 99%
“…Gene expression profiling data from many tissues have led to the identification of genes that are expressed in many types of stem cells, some of which are required for self-renewal [2][3][4][5]. Sox2 [6][7][8], Zfx [9], Jam-B [10], and nucleostemin [11] are examples of genes expressed in a variety of stem cells. Nucleostemin is a nucleolar GTPbinding protein that regulates cell cycle progression and is required for early embryogenesis, with deletion of the gene resulting in embryonic lethality at around 3.5 days postcoitum (d.p.c.)…”
Section: Introductionmentioning
confidence: 99%
“…The insights gained by using an in vitro cell system that expresses only one JAM isoform can guide studies of liver development in vivo, where the lack of liver phenotypes in any of the three JAM knockout mice points to overlapping functions for the protein (8,21,56). Future studies using the KD cells to express different JAM isoforms and mutant constructs should also provide further understanding of this protein's role in the complex polarity of hepatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although epithelial functions have been disrupted by JAM-A knockdown (KD) in cell culture models of simple epithelia and recently in cultured hepatic cells (35,54), gene knockout studies of individual JAMs in mice have shown no major defects in development or function of epithelia, most likely a consequence of gene redundancy (8,21,56). Nonetheless, results from the in vitro studies suggest that JAM plays an essential and early role in TJ formation (17,26,38), since it was found at primordial cell-cell contact sites in a bronchial epithelial cell line (31).…”
mentioning
confidence: 99%
“…in the bone marrow, with their expression decreasing during the acquisition of a more differentiated state (Nagamatsu et al, 2006;Sakaguchi et al, 2006;Sugano et al, 2008;Praetor et al, 2009). Furthermore JAM-A expression has been reported to be high on undifferentiated HC11 mammary epithelial cells relative to differentiated cells (Perotti et al, 2009).…”
Section: J a M -A J A M -B J A M -C A N D J A M -4 H A V E B E E mentioning
confidence: 99%